2014
DOI: 10.1155/2014/468751
|View full text |Cite
|
Sign up to set email alerts
|

Soil Erosion Prediction Using Morgan-Morgan-Finney Model in a GIS Environment in Northern Ethiopia Catchment

Abstract: Even though scientific information on spatial distribution of hydrophysical parameters is critical for understanding erosion processes and designing suitable technologies, little is known in Geographical Information System (GIS) application in developing spatial hydrophysical data inputs and their application in Morgan-Morgan-Finney (MMF) erosion model. This study was aimed to derive spatial distribution of hydrophysical parameters and apply them in the Morgan-Morgan-Finney (MMF) model for estimating soil eros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…hardware and software, data and skilled man) and financial limitation. The spatial distribution of the hydrophysical parameter is the source of evidence about soil erosion procedure and designing appropriate soil and water conservation, it can be emerged by GIS (Tesfahunegn et al, 2014).…”
Section: Contribution Of Gis and Rs In Watershed Delineationmentioning
confidence: 99%
See 2 more Smart Citations
“…hardware and software, data and skilled man) and financial limitation. The spatial distribution of the hydrophysical parameter is the source of evidence about soil erosion procedure and designing appropriate soil and water conservation, it can be emerged by GIS (Tesfahunegn et al, 2014).…”
Section: Contribution Of Gis and Rs In Watershed Delineationmentioning
confidence: 99%
“…In other views, improper LULCC is directly or indirectly connected with the most commonly known of USLE or RUSLE parameters. They also called spatial variability and they are a key determinate of soil erosion risks (Tesfahunegn et al, 2014). Many scholars confirmed that land degradation in form soil erosion influenced by biophysical factors most of them are included in USLE or RUSLE factors.…”
Section: Gis and Rs For Identifying The Cause Of Soil Erosionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sampling was focused mainly on this plow layer because this is the depth where changes in most soil properties are expected to occur due to short-term soil management practices (Tesfahunegn et al, 2014). In addition to this, tef root system is shallow especially at the early stage of the crop and its dense fibrous roots are generally concentrated at the topsoil depth for using soil moisture and nutrients (Ketema, 1993).…”
Section: Soil Moisture Determinationmentioning
confidence: 99%
“…Due to the simplicity, flexibility and strong physical base, several researchers have implemented the MMF (Morgan et al ., ) and the revised‐MMF(RMMF) (Morgan, ) models for estimating annual soil loss in a wide range of environment across the world, such as in Malaysia (Morgan and Finney, ), Indonesia (Besler, ), Nepal (Shrestha, ), the Rocky Mountains of the USA (Morgan, ), Nepal (Morgan, ), Kenya and Tanzania (Vigiak et al ., ), Hungary (Hudek et al ., ), Spain (López‐Vicente and Navas, ; López‐Vicente et al ., , ), China (Li et al ., , ) and Italy (Svorin, ); Ethopia (Tesfahunegn et al ., ); Thailand (Shrestha et al ., ); India (Jasrotia and Singh, ; Pandey et al ., ; Kothyari et al ., ; Korada and Vala, ).…”
Section: Introductionmentioning
confidence: 99%